PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2019-2022 - nuryanti, nuryanti; rizca (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
The problem in this study is the influence of Current Ratio (CR), Debt to Equity Ratio (DER) and Return on Equity (ROE) on share prices in property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. This research was conducted to determine the effect of financial performance on stock prices in property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. The variables used in this study are Current Ratio (CR), Debt to Equity Ratio (DER) and Return on Equity (ROE) as independent variables and stock price as the dependent variable. The type of research used in this study is a quantitative approach and the research design used is an exploratory research design. The population used is property and real estate companies that are on the main board listed on the Indonesia Stock Exchange (IDX) in 2019-2022. Purposive sampling method is the method used in sample selection in this study so as to get samples as many as 16 companies. Data collection techniques use secondary data carried out with documentation methods. The data used are financial statements on the Indonesia Stock Exchange for 2019-2022 through the www.idx.co.id website and through the id.investing.com website. The data analysis techniques used are classical assumption test, linear regression coefficient test, correlation coefficient test, determination coefficient test and hypothesis test. The results of this study show that partially the variables of current ratio (CR) and debt to equity ratio (DER) have a significant negative effect on stock prices. While partial return on equity (ROE) does not have a significant effect on stock prices. Simultaneously, the current ratio (CR), debt to equity ratio (DER) and return on equity (ROE) have a significant effect on stock prices